Study on pyrolysis mechanism of 1,7-diacetoxy-2,4,6-trinitro-2,4,6-triazaheptane (BSX) - Ruxin Zhang; Liang Qin; Hongping Su; Luting Wang; Xiaoli Duan; Lizhen Chen; Jianlong Wang (Arabian Journal of Chemistry, 2023)
The thermal decomposition process of 1,7-diacetoxy-2,4,6-trinitro-2,4,6-triazaheptane (BSX) was studied by TG-DSC, TG-MS, TG-FTIR technology and ReaxFF molecular dynamics (ReaxFF MD) simulation. The decomposition activation energy of BSX was calculated according to the test results of TG-DSC. The main thermal decomposition products of BSX were determined by combining experiments and simulations, and the possible thermal decomposition pathways were analyzed. The results showed that the decomposition activation energy of BSX is 161 ± 2.6 kJ·mol−1; The thermal decomposition of BSX may generate the main intermediate products C8H14N5O8, C4H7NO2, C2H3O2, HNO2, NO2 and NO, etc., and the intermediate products continued to decompose to generate the final products CH2O, CO2, CO, H2O and N2; The reaction rate constants of each stage of BSX were calculated, and the possible thermal decomposition pathways of BSX were obtained: BSX → C8H14N5O8 + NO2 → C5H9N3O4 + C4H7N4O6 + C4H7NO2 + C3H5N2O4 → C2H3O2 + C2H3O + CH2O + CO2 + CO + H2O + HNO2 + N2O2 + NO2 + NO + H + OH + … → CH2O + CO2 + CO + H2O + N2 + … This study contributes to a deeper understanding of the decomposition process of BSX after heating and has specific significance for reducing the thermal hazard of the BSX pyrolysis process.